Occupational exposures to solvents and metals are associated with fixed airflow obstruction - Sheikh M Alif; Shyamali C Dharmage; Geza Benke; Martine Dennekamp; John A Burgess; Jennifer L Perret; Caroline J Lodge; Stephen Morrison; David P Johns; Graham G Giles; Lyle C Gurrin; Paul S Thomas; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: This study investigated the associations between occupational exposures to solvents and metals and fixed airflow obstruction (AO) using post-bronchodilator spirometry. METHODS: We included 1335 participants from the 2002-2008 follow-up of the Tasmanian Longitudinal Health Study. Ever-exposure and cumulative exposure-unit (EU) years were calculated using the ALOHA plus job exposure matrix (JEM). Fixed AO was defined as post-bronchodilator forced expiratory volume in one second (FEV1)/forced vital capacity (FVC) <0.7 and FEV_1/FVC<lower limit of normal. Diffusing capacity of the lung for carbon monoxide (DLCO) was combined with FEV_1/FVC<0.7 to define fixed AO plus low DLco. Multinomial regressions were used to estimate associations adjusting for possible confounders. RESULTS: Ever-exposure to metals was associated with fixed AO [relative risk (RR) 1.71, 95% CI 1.03-2.85] and fixed AO lower limit of normal (RR 1.67, 95% CI 1.00-2.78). Women had lower cumulative EU years to chlorinated solvents [mean 20.9, standard deviation (SD) 13.4] than men (mean 28.6, SD 36.9). However, the risk of developing fixed AO and fixed AO plus low DLCO associated with each cumulative EU year of chlorinated solvents were higher among women than men (RR 1.08 versus 0.99, P-value for effect measure modification=0.006; RR 1.08 versus 1.00, P-value for effect measure modification=0.02). CONCLUSIONS: We have shown ever-exposure to metals and chlorinated solvents are important risk factors for fixed AO. The effects for solvents were strongest among women. Preventive strategies need to be followed to reduce these exposures at the workplace.